2019
DOI: 10.1055/a-1024-3789
|View full text |Cite
|
Sign up to set email alerts
|

Needle-knife fistulotomy vs. standard biliary sphincterotomy for choledocholithiasis: common bile duct stone recurrence and complication rate

Abstract: Background and study aims  With common bile duct (CBD) stones, access to the CBD can be achieved through the papilla orifice followed by standard biliary sphincterotomy (SBS), or through precut fistulotomy (PF) in case of difficult cannulation. The two methods alter papilla anatomy differently, potentially leading to a different rate of stone recurrence. No data have been published on stone recurrence after PF in patients with CBD stones. The aim of this study was to evaluate CBD stone recurrence, reinterventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
3
13
0
1
Order By: Relevance
“…Studies showed that NKF is effective in achieving biliary access when difficult biliary cannulation is present (13) . Recent studies defend its early implementation during challenge cases (14) . Another common technique is the needle-knife precut sphincterotomy when the incision is initiated from the papillary orifice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that NKF is effective in achieving biliary access when difficult biliary cannulation is present (13) . Recent studies defend its early implementation during challenge cases (14) . Another common technique is the needle-knife precut sphincterotomy when the incision is initiated from the papillary orifice.…”
Section: Discussionmentioning
confidence: 99%
“…Both patient and technique factors were used to identify the predictors associated with the failure of initial NKP 25 . Patient factors were similar to those of difficult biliary cannulation, including age, sex, the diameter of CBD, major papilla status, and indications of ERCP 4 , 5 .…”
Section: Methodsmentioning
confidence: 99%
“…The indications of ERCP included choledocholithiasis, malignant or benign biliary stricture, bile leak, and suspected Sphincter of Oddi dysfunction. Technique factors, based on few individual reports, were decided on consensus by the authors, including the endoscopists’ experience in NKP, bleeding during NKP, early vs. late pre-cut, and placement of a P-duct stent before NKP 25 27 . Bleeding during NKP was defined as bleeding induced by NKP, which could interfere with or eventually cause interruption of NKP (due to blocking of the endoscopic view, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Whether precut fistulotomy, by retaining integrity of the distal papillary sphincter, could also act as a potential risk factor for CBD stones recurrence remains unknown. This question is being elucidated in the current issue of Endoscopy International Open by Archibugi et al [9].…”
mentioning
confidence: 98%
“…Whether precut fistulotomy, by retaining integrity of the distal papillary sphincter, could also act as a potential risk factor for CBD stones recurrence remains unknown. This question is being elucidated in the current issue of Endoscopy International Open by Archibugi et al [9].In their retrospective study the authors included 85 patients with a diagnosis of choledocholithiasis treated by CBD clearance after PF. These cases were age and sex matched with respective patients fulfilling inclusion criteria but undergoing conventional endoscopic biliary sphincterotomy (BS).…”
mentioning
confidence: 99%